AWARENESS AND ACCEPTANCE LEVEL OF CUSTOMERS REGARDING ELECTRONIC BANKING SERVICE IN SELECTED PUBLIC AND PRIVATE INDIAN BANKS - Prof. Mahesh Chand Garg, Parveen Kumar (International Journal of Advanced Science and Technology, 2020)
This purpose of this paper is to know the awareness level and acceptance level of customers regarding electronic banking service in selected public and private Indian banks separately. For this study, a sample of top 10 public and top 10 private scheduled commercial banks has been taken from three selected city of NCR. These banks were selected on the basis of maximum profitability in India. A sample size of 600 customers selected taking 10 customers from each bank by using non-probability convenience sampling through well-structured questionnaire and 578 questionnaires were used in final analysis. The study found that the awareness level and acceptance level of customers regarding e-banking services such as Online Banking, ATM/Debit Cards, Credit Cards, Forex Cards, Prepaid Cards, Mobile Banking, SMS Alerts / Email Alerts, Electronic Fund Transfer, Electronic Clearing System, and Real Time Gross Settlement System in selected private sector banks was higher than selected public sector banks. Similarly, the awareness level and acceptance level of customers regarding e-banking services such as Electronic Wallets, UPI App., Passbook Updating Machine and Electronic Cheque Deposit Machine in selected public sector banks was higher than selected private sector banks.